Disappearance of aura symptoms in patients with hemiplegic migraine after patent foramen ovale closure: a case report and literature review - Wang, Pian; Yao, Fengyou; Zhang, Hongbo; Yu, Qian; Wang, Yan (Frontiers in Neurology, 2023)
Hemiplegic migraine (HM) can cause significant functional impairment and negatively affect the quality of life of affected individuals. Emerging evidence suggests an association between migraines and congenital patent foramen ovale (PFO), which is a small opening between the atria of the heart that normally closes shortly after birth. This report describes a 34 years-old woman with sporadic hemiplegic migraine (SHM) who was diagnosed with PFO. Following percutaneous PFO closure, her hemiplegic symptoms disappeared, but her headache exacerbated. After 3 years of follow-up, her headache severity gradually reduced, and the frequency remained consistent at 2–3 times per year with no aura symptoms. This case highlights the dissociation between the resolution of hemiplegic symptoms and the persistence of headaches after PFO closure in sporadic HM. Patients with HM may experience changes in aura symptoms and headache severity after PFO closure. Before performing PFO closure in patients with hemiplegic migraine, the indications should be thoroughly understood.